2018
DOI: 10.1155/2018/4730896
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Injections in the Treatment of Diabetic Foot: A Systematic Review and Meta‐Analysis

Abstract: Context The role of traditional Chinese medicine injections (TCMIs) in diabetic foot (DF) has not been well estimated. Objective To evaluate the clinical effective rate, safety, and the financial cost of TCMIs in treating DF and ulcer wound healing. Methods We searched PubMed, Embase, CENTRAL, China National Knowledge Infrastructure (CNKI), VIP database, and Wanfang database from inception to May 2018 to find all randomized control trials (RCTs) related to TCMIs in DF treatment. The search items were “Traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Thus, there is an utmost need for the development of new therapeutic agents that can exert multifunctional potential on the various phases of wound healing. A systematic review reported that therapeutic moieties of natural origin could be implicated in the management of impaired DFU [15]. Boswellia serrata Roxb.…”
Section: Wound Healing Potential Of the Standardized Extract Of Boswementioning
confidence: 99%
“…Thus, there is an utmost need for the development of new therapeutic agents that can exert multifunctional potential on the various phases of wound healing. A systematic review reported that therapeutic moieties of natural origin could be implicated in the management of impaired DFU [15]. Boswellia serrata Roxb.…”
Section: Wound Healing Potential Of the Standardized Extract Of Boswementioning
confidence: 99%
“…Previous study found that a group of traditional Chinese medicine (TCM) ( e.g. , herbal medicine foot bath decoction[ 5 ], TCM injections[ 6 , 7 ], Chinese herbal medicine ulcer oil[ 8 ], moxibustion[ 9 ], Astragali Radix and Rehmanniae Radix Mixture[ 10 ], the peptide compounds of Wuguchong[ 11 ], Astragali Radix and Rehmanniae Radix[ 12 , 13 ]) played an important role in the treatment of the disease. Some study also found that interventional radiology plays a crucial role in the treatment of diabetic foot disease[ 14 ].…”
Section: To the Editormentioning
confidence: 99%
“…In recent years, most diabetic foot patients in China are adopting TCM and western medicine[ 5 , 15 ]. A series of systematic review articles showed that TCM can increase the clinical effective rate of conventional therapies by 27%[ 6 ], regulate the signaling pathways to promote diabetic wound healing[ 16 ]. An experiment on albino Wistar rats found that Astragali Radix and Rehmanniae Radix in the ratio of 2:1 significantly enhance the circulating CD34+/VEGFR2+/CD45-EPCs levels in diabetic foot ulcer[ 17 ].…”
Section: To the Editormentioning
confidence: 99%
“…Research on TCM for chronic non-communicable diseases has recently developed rapidly[ 40 ]. In particular, studies have reported that oral administration or injection of TCM herbal-based agents as an additional treatment to conventional therapies is beneficial to DFU healing[ 41 , 42 ]. Meanwhile, in recent years, complementary modalities have also demonstrated therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%